Co-Administration of Naringenin with Isoproterenol Alters Cardio-Hepatic Bioactivity in Experimental Animal Models - Nkanu, Etah E. (European Journal of Applied Sciences, 2025)
Isoproterenol is a beta-1 adrenergic agonist that has over time been used in the management of cardiovascular cases. Above optimal dosage, it may lead to altered liver function and cardiac activity shown by variations in heart and liver biomarkers. This study aimed at investigating the effect of co-administration of isoproterenol and naringenin on cardio-hepato activity and when administered at separate treatment periods. Female Wistar rats were randomly divided into four groups of five rats. Group A (Control) received normal saline, group B received 18mg/kg body weight of Isoproterenol in saline (given subcutaneously, for one week), Group C received 18mg/kg of isoproterenol and naringenin (40mg/kg orally), Group D received Isoproterenol (18mg/kg) for one week and supplemented with naringenin for two weeks. Treatment lasted for 21days. Blood samples were collected for biochemical analyses, heart and liver were collected for histological analyses. Plasma Creatine kinase, Troponin, Lactate dehydrogenase, Malondealdehyde, liver enzymes, all increased in isoproterenol administration alone; dropped with co-treatment with naringenin except for ISO+NRG, but increased in activity at 1week isoproterenol treatment and then followed by two weeks naringenin treatment. Histological alterations were prominent in heart and liver of rats in all treatment groups showing moderate aggregate of myocardial inflammation with loss of cardiac tissues and also infiltration of inflammatory hepatic cells with periductal fibrosis. This results suggest that co-administration of isoproterenol with naringenin has in vivo efficacy and has the potential to improve cardiac-hepatic function, but may fail to ameliorate tissue injury at separate treatment periods.